Pengembangan UMKM Melalui Pelatihan Pengolahan Hidangan Berbasis Bahan Makanan Lokal di Kabupaten Badung - Dwik Suwarnata Triana; Ida Ayu Etsa Pracintya; I Made Darsana (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to develop the capacity of Micro, Small, and Medium Enterprises (MSMEs) stakeholders in Badung Regency through training on processing dishes based on local food ingredients. Using a participatory training method which included counseling, demonstrations, hands-on practice, and mentoring. The study focused on improving technical skills as well as knowledge of hygiene standards and product marketing. The results showed an increase in the ability of MSME stakeholder to process local ingredients into innovative and appealing culinary products that meet market needs, while also strengthening sanitation and product quality aspects to make them more attractive to consumers. The participatory approach also encourages MSME stakeholders to actively contribute to the product development and marketing strategies, resulting in increased competitiveness and business sustainability. This study provided important contributions to MSME empowerment and the development of the local economy based on the potential of local natural resources.